Combined treatment with oestradiol benzoate, d-cloprostenol and oxytocin permits cervical dilation and nonsurgical embryo recovery in ewes - Fonseca, Jeferson Ferreira da; Zambrini, Fabiana Nunes; Guimaraes, Jose Domingos; Silva, Marcio Roberto; Franco Oliveira, Maria Emilia [UNESP]; Brandao, Felipe Zandonadi; Bartlewski, Pawel Mieczyslaw; Goncalves Souza-Fabjan, Joanna Maria (Wiley-Blackwell, 2019)
Contents This study examined the feasibility of transcervical embryo recovery after the hormonal treatment to induce cervical dilation, following the 7-day oestrous synchronization protocol in multiparous Santa Ines ewes. A total of 23 cyclic ewes received two doses of 37.5 mu g of d-cloprostenol by latero-vulvar route 7 days apart. After the second injection of d-cloprostenol, the ewes were checked for oestrus (every 12 hr) and then mated by fertile rams throughout the oestrous period. All ewes received 37.5 mu g of d-cloprostenol (latero-vulvar) and 1 mg of oestradiol benzoate by either intramuscular (EBim group; n = 12) or intravaginal (EBivg group; n = 11) route 16 hr before embryo flushing. Twenty minutes before the flushing, 50 IU of oxytocin were administered intravenously. The oestrous response (i.e., the percentage of ewes that showed signs of oestrous behaviour after the second d-cloprostenol injection) was 91.3% (21/23). The proportion of successfully penetrated ewes (81.8% compared with 80.0%), the mean duration of embryo flushing (24.7 +/- 2.0 min compared 26.2 +/- 1.9 min), the flushing fluid recovery rate (94.8 +/- 1.3% compared with 91.0 +/- 2.9%) and the average number of structures recovered per ewe (0.5 +/- 0.4 compared with 0.8 +/- 0.4) did not vary (p > 0.05) between the EBim and EBivg groups. Viable embryos were recovered from 41.2% (7/17) of successfully penetrated ewes. It can be concluded that nonsurgical (i.e., transcervical) embryo collection can be performed in oestrous-synchronized Santa Ines ewes pretreated with d-cloprostenol, oxytocin and oestradiol benzoate, with the latter hormone administered by either the intramuscular or intravaginal route.
Keywords: cervical dilation; cloprostenol; oestradiol benzoate; oxytocin; sheep; transcervical embryo collection